Quality Perception in Utility Provision : A Conceptual and Empirical Approach - World Bank (Washington, DC, 2013)
The perspective of this study is not only academic but also practical. As regards the academic aspect, this work will explore the professional literature related to quality perception and, particularly, the conceptual discussion about the object of satisfaction measurement in a market research involving utility customers and their perception of service quality. As the immediate consequence of this theoretical review, the study intends to develop the general guidelines of a survey meeting the best standards from the point of view of the theory. In the second place, this work seeks to carry out some measuring so as to empirically evaluate the principles analyzed in the previous section. In light of these purposes, the work is structured as follows: chapter one deals with the theme from a theoretical perspective and reviews literature arising from disciplines such as marketing and economics. Chapter two develops the general structure of a survey with suggestions about its construction and design that will be taken into account when performing the appropriate field studies; chapter three presents the results of the field studies. Finally, the study shows the conclusions drawn.